The transformation of spiritual digital literacy: strategies of islamic education teachers in instilling islamic educational values in the era of cyberbullying - Sigit Utomo; Nur Alfi Muanayah; Dewi Khalimaturrohmah; Dwi Marsha Zahrotul Jannah; Naila Sofiyatun Nisa; Riska Febi Saputri; Husna Nashihin (At Turots: Jurnal Pendidikan Islam, 2024)
The rapid advancement of digital technology has brought significant shifts in educational paradigms, especially in the realm of Islamic Education (PAI). In the midst of growing cyberbullying phenomena, the role of PAI teachers is not only to educate but also to instill and preserve Islamic values through spiritual digital literacy. This study explores how spiritual digital literacy is transformed and strategically utilized by PAI teachers to address ethical and moral challenges in the digital age. Using a qualitative library research method with thematic content analysis, various scholarly works, journal articles, and educational policy documents were analyzed to identify effective strategies employed by teachers. The findings indicate that spiritual digital literacy must be consciously cultivated to empower students in facing the negative impacts of cyberspace, including cyberbullying. PAI teachers are shown to act as value-driven digital facilitators who integrate faith-based ethics into online learning environments, creating safe, reflective, and spiritually enriching educational experiences.